A Research Paper on Digital Transformation in Car Buying Process: Understanding Usage Intentions with the Technology Acceptance Models - et. al., Rekha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital interventions have affected every business and product category. Consumers are making use of digital channels and platforms to research, explore, review and buy the routine items like grocery to speciality and high involvement products involving significant outlay such as Car. However, it remains yet to be researched adequately by the researchers in an emerging economy context, whether the purchase of a product like car has been affected in same way as that of routine items by the digital channels. This study compares the most popular intentions-based models namely technology acceptance model (TAM) with the decomposed theory of planned behaviour (DTPB) to predict the intentions of Indian car buyers to employ digital marketing communication while making a car buying decision. The study is of great relevance to the academicians because it provides a peep into the role of consumer’s intention in shaping consumer behaviour. Not many studies have applied the intention based models in Indian passenger car market especially in technology mediated environment. The study has not only seen the application of intention-based models in a relatively unexplored category, but also puts forwards the most suitable model that could be used by the marketers to predict the usage intentions and actual usage of digital marketing communication thereafter, while taking a car buying decision. Primary data was obtained from 500 car buyers consisting of both actual and potential buyers from Delhi. Structural equation modeling was used to evaluate and compare both the models in terms of overall fit, explanatory power and significance. The results of the study revealed that digital channels have transformed the car buying process and DTPB was more successful model in predicting Indian car buyers’ intentions to use digital marketing communication while buying a car.